A Diary Study of Information Capture in Working Life - Brown, Barry A. T.; Sellen, Abigail; O'Hara, Kenton (CHI 2000, April 1-6, 2000, The Hague, Amsterdam, 2000)
Despite the increasing number of new devices entering the market allowing the capture or recording of information (whether it be marks on paper, scene, sound or moving images), there has been little study of when and why people want to do these kinds of activities. In an effort to systematically explore design requirements for new kinds of information capture devices, we devised a diary study of 22 individuals in a range of different jobs. The data were used to construct a taxonomy as a framework for design and analysis. Design implications are drawn from the framework and applied to the design of digital cameras and hand held scanners.